2017
DOI: 10.1007/s12016-017-8647-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Food Allergy: a Comprehensive Review

Abstract: Food allergy imposes a severe global health burden, and thus, there is a dire need for safe and effective treatments. Allergen-specific immunotherapy (AIT) is currently the only approach to restore immune tolerance through administrating increasing doses of allergen extracts. Unfortunately, the development of AIT for food allergies has been impeded by the frequent anaphylactic side effects during the course of treatment. The emergence of component-resolved diagnosis has greatly improved our ability to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 196 publications
0
27
0
Order By: Relevance
“…In cow's milk, egg and peanut allergies, there is extensive literature on the clinical efficacies of different OIT, SLIT and EPIT regimens [50,97], as well as novel pioneering studies on diagnostic and AIT strategies. The FAST project aiming at testing hypoallergens against fish and peach allergies is actively underway [98].…”
Section: Discussionmentioning
confidence: 99%
“…In cow's milk, egg and peanut allergies, there is extensive literature on the clinical efficacies of different OIT, SLIT and EPIT regimens [50,97], as well as novel pioneering studies on diagnostic and AIT strategies. The FAST project aiming at testing hypoallergens against fish and peach allergies is actively underway [98].…”
Section: Discussionmentioning
confidence: 99%
“…Allergen-specific immunotherapy (AIT) is the only disease-modifying treatment that is currently available for respiratory allergies. However, AITs for IgE-mediated food allergies have significant efficacy limitations, associated side effects, debatable ability to achieve long-term protection following discontinuation of therapy, as well as adherence challenges [5,6,7,8,9,10]. No active immunotherapy for shellfish allergy is currently under investigation, even amidst the increasing prevalence of this type of food allergy.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to allergy prediction, the impact of IgG‐, especially IgG 4 ‐ , binding epitopes in AIT monitoring has been investigated more intensively. In general, patients, irrespective of the AIT outcome, showed an increase in allergen‐specific IgG 4 levels as well as a temporary increase in IL‐10 secreting FoxP3‐positive Treg cells controlling a class switch to IgG 4 and a decrease in sIgE levels . In a peanut AIT trial, newly formed IgG 4 antibodies had specificities partly identical to identified IgE‐binding epitopes.…”
Section: Impact Of Ige‐ and Igg‐binding Epitopes In Food Allergy Immumentioning
confidence: 98%
“…In general, patients, irrespective of the AIT outcome, showed an increase in allergen-specific IgG 4 levels as well as a temporary increase in IL-10 secreting FoxP3-positive Treg cells controlling a class switch to IgG 4 and a decrease in sIgE levels. [101][102][103][104] In a peanut AIT trial, newly formed IgG 4 antibodies had specificities partly identical to identified IgE-binding epitopes. Simultaneously, the total sIgE decreased, although, as also shown in CMA AIT trials, new IgE specificities were developed.…”
Section: Epitopes In Food Alle Rgy Immunotherapy Monitoringmentioning
confidence: 99%